Understanding Bharati Mukherjee - Maxey, Ruth (Book collections on Project MUSE., 2019)
"Bharati Mukherjee was an important, bold, pioneering American writer. Born in Calcutta, India on July 27, 1940 to Sudhir Lal Mukherjee and Bina (nee Chatterjee), a Bengali Brahmin couple, the young Bharati--the middle of three daughters--enjoyed a privileged early life. Mukherjee's father was a biochemist who ran a successful pharmaceutical company and supported a wide network of some fifty relatives all based within the same house in Ballygunge, south Calcutta. A precociously intelligent child, Mukherjee was always highly literate, stimulated by her parents to read and study. Consuming books in a quiet corner was often a refuge from the claustrophobic demands of traditional Indian joint family living, and she began writing stories as a young child. Mukherjee was inspired by the storytelling of her paternal grandmother and her mother. Indeed, she consistently paid tribute to Bina, who proudly defended and encouraged Mukherjee and her two sisters, Mira and Ranu, against a patriarchal backdrop of ridicule from Bina's older, female in-laws for having borne Sudhir no sons."--